SISTEM PENJADWALAN KEBERANGKATAN DAN PEROLEHAN PENUMPANG BUS ANTARKOTA - Subandi Subandi; Desta Nur Fajrini; Aang Gunawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study aimed at examiningthe effect of bus fleet scheduling on intercity bus passenger’s gaining. Good fleet scheduling with the difference in departure time between two small and stable sequential buses will produce good passenger gaining as well. The research method used linear regression. The results of this study show the effect of bus fleet scheduling on passenger gaining in the linear regression equation Y = 90.622 - 0.53X. Besides, the correlation of the two variables is quite strong in the negative direction with r = -0.59. The greater the difference in departure time of two consecutive buses, the lower the passenger bus gaining. Finally, this study proves that the effect of bus fleet scheduling on bus passenger gaining between cities is small (r2 = 34%) and not significant (t count -0.66 is smaller than t table 12.706).